MISCELLANEOUS BOTANICAL NOTES 1* - A.J.G.H KOSTERMANS (Research Center for Biology, 1960)
1.Papuodendron C. T. White is reduced to Hibiscus L.; the species is renamed:H. papuodendron Kosterm.2. Hibiscus hooglandianus represents a new species from New Guinea.3. New species in Pentace: P. microlepidota Kosterm., P. paludosa Kosterm. and P. adenophora Kosterm.4. Parapentace Gagnepain is included in Burretiodendron Rehd. As the species of Parapentace were published without latin diagnosis, the following new species of Burretiodendron are presented: B. tonkinensis Kosterm. and B. brilletii Kosterm.5.Two new species of Heritiera (H. rumphii Kosterm. and H. ornithocephala Kosterm.) are described; additional notes on H. littoralis from Madagascar, H. longi petiolata and H. arafurensis are presented.6. Heritiera burmensis Kosterm. is reduced to a synonym of H. macrophylla Kurz.7.Sterculia cubensis Urb. is referred to Hildcgardia; the curious distributional area of Hildegardia is stressed.8. A note on Hildegardia erythrosipkon Kosterm. is presented.9.Sterculia ankaranensis Arenes is relegated to Hildcgardia.10. Sterculia heritieriformis Arenes represents a mixture of Heritiera littoralis and Firmiana colorata.11. Sterculia guppyi Greenwood is a synonym of Firmiana diversifolia A. Gray.12. Ficus serp-yllifolia Blume belongs actually to Apocynaceae and is renamed: Micrcchites serpyllifolia (Bl.) Kosterm. It is suggested that M. radicans Markgr. is conspecific with this wide-spread species.13. Ortholobium Gagnepain, being inadmissable under the Rules (no latin diagnosis)is replaced by Cylindrokelupha Kosterm. The following new species are presented: C. poilanei Kosterm., C. platyphylla Kosterm.; C. annamcnse Kosterm. and C. chevalieri Kosterm.